Eco-Friendly Improvement of Comprehensive Engineering Properties of Collapsible Loess Using Guar Gum Biopolymer - Yuesong Zheng; Tianhao Li; Daokun Qi; Xiaojuan Xi; Fengzu Peng; Shijun Ding; Zhibao Nie; Xin Hu; Gaowen Zhao; Bo Xiao; Yake Tang; Wenhui Wang (Buildings)
Collapsible loess is characterized by its unique soil-forming environment, mineral composition, and microstructure, resulting in poor engineering properties such as high water sensitivity, high collapsibility, high compressibility, and low strength. To improve the poor engineering properties of collapsible loess, we selected a suitable eco-friendly material—guar gum (GG)—for its improvement and reinforcement, and investigated the improvement effect of different GG dosages (0.5~1.5%) and curing ages (0~28 days) on collapsible loess. The mechanical properties of soil samples were determined by direct shear tests, unconfined compressive strength tests, and splitting tests. The water stability of soil samples was evaluated by both cube and sphere crumb tests. SEM and EDS analyses were also conducted to determine the microstructural and mineral changes in soil. The results indicate that the incorporation of GG is beneficial to inhibit the collapsibility of the soil and improves the water stability and strength of the soil. The collapsibility coefficient of loess is reduced to below 0.015 when 0.75% and above of GG is admixed, which is considered a complete loss of its collapsibility. When the GG dosage increases from 0% to 1.25%, the compressive strength and tensile strength of the soil samples increase by 43.5% and 34.9%, respectively. However, by further increasing the GG dosage to 1.5%, the compressive strength and tensile strength decrease by 3.8% and 6% compared to those with 1.25% GG. This indicates that the strength of the specimens shows an increasing trend and then a decreasing trend with the increase in GG dosage, and 1.25% GG was found to be the best modified dosage. Microstructural and mineral analyses indicate that the addition of GG does not change the mineral composition of loess, but, rather, it significantly promotes the agglomeration and bonding of soil particles through cross-linking with Ca2+ ions in the soil to form a biopolymer network, thus achieving a reliable reinforcement effect. Compared with the existing traditional stabilizers, GG is a sustainable and eco-friendly modified material with a higher low-carbon value. Therefore, it is very necessary to mix GG into collapsible loess to eliminate some of the poor engineering properties of loess to meet engineering needs. This study can provide test support for the application and promotion of GG-modified loess in water agriculture and road engineering.